Validitas E-Modul Hidrokarbon Berbasis Guided Discovery Learning untuk Pembelajaran Kimia Kelas XI SMA/MA - Najmi Elsoraya; Yerimadesi Yerimadesi (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
This study aims to develop and analyze the validity of the developed e-module. This research is a type of educational design research using the Plomp model. At the validation stage, the feasibility of the e-module was assessed by three lecturers from the chemistry department, FMIPA UNP and two teachers from SMA Negeri 1 Lintau Buo. The validation results were obtained from experts consisting of three chemistry lecturers from FMIPA UNP and two chemistry teachers at SMA N 1 Lintau Buo. The research instrument used in this study was a validity questionnaire which was analyzed using the Aikens'V formula. The validation results were obtained from experts. The validation stage was carried out in two stages. The first stage obtained an average V value of 0.82 with an average content component validity with a V value of 0.75 (invalid), the linguistic component with a V value of 0. 88 (valid), the presentation component with a V value of 0.78 (invalid), the graphic component with a V value of 0.85 (valid) and the programming aspect with a V value of 0.84 (valid). The average validity obtained in the second validation stage is 0.86 (valid) with an average content component validity with a V value of 0.85 (valid), the linguistic component with a V value of 0.88 (valid), the presentation component with a V value of 0.88 (valid). V 0.83(valid), component with V value 0.85(valid) and programming aspect with V value 0.87(valid). After validation, the next step is a one to one evaluation test with a one to evaluation questionnaire instrument to three class XI students with different abilities. The conclusion from the research results is that the hydrocarbon e-module based on guided discovery learning for class XI SMA/MA which was developed is valid and can be continued for further research.